(untitled) (PSIKOLOGI KONSELING, 2025)
The task of early adult development is to find and run a job and build relationships in a social environment. Self-openness is important for psychology students both in the learning process and in interaction with others. Individuals who do not have self-disclosure skills will have difficulty communicating with other individuals. Introverted individuals are individuals who tend to close themselves off and not open up. Students should have high self-disclosure, but the fact is that students who have self-disclosure in the low category are not few. This study aims to see the effectiveness of assertive training to increase self-disclosure in introverted students. Participants in this study were introverted students majoring in psychology in the city of Makassar who had low-to-medium self-disclosure scores. The method used in this study is a true experiment. The data was analysed using an independent sample t test. The results of the study show that assertive training is effective in increasing self-disclosure in introverted students. The pretest value before treatment was shown with a mean of 27.63 and the post-test value after treatment was given with a mean of 39.50 with a significance value of 0.01 (p<0.05).